The effects of wakeful rest on memory consolidation in an online memory study - King, Olivia; Nicosia, Jessica (Frontiers in Psychology, 2022)
Memory consolidation is the process in which memory traces are strengthened over time for later retrieval. Although some theories hold that consolidation can only occur during sleep, accumulating evidence suggests that brief periods of wakeful rest may also facilitate consolidation. Interestingly, however, Varma et al. (2018) reported that a demanding 2-Back task following encoding produced similar performance to a wakeful reset condition. We tested whether participants’ recall would be best following a wakeful rest condition as compared to other distractor conditions, consistent with the extant wakeful rest literature, or whether we would replicate the finding from Varma et al. (2018) such that participants’ memory benefitted from both a Rest and 2-Back task following encoding. Across two experiments, we used similar (Experiment 1) and the same (Experiment 2) encoding material as Varma et al. (2018), employed a wakeful rest condition adapted for online testing, and compared participants’ recall across post-encoding conditions. In the first experiment, we used a between-subjects design and compared participants’ cued recall performance following a period of wakeful rest, a 2-Back task, or a Rest + Sounds condition. The second experiment more closely replicated the experimental design used in Varma et al. (2018) using a within-subjects manipulation. Ultimately, our findings more consistently aligned with the canonical wakeful rest finding such that recall was better following the Rest condition as compared to all other post-encoding conditions. These results support the notion that wakeful rest may allow for consolidation by protecting recently encoded information from interference and thereby improving memory performance.